2018
DOI: 10.1038/s41598-018-35605-y
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptomic profiling of the clonal Leymus chinensis response to long-term overgrazing-induced memory

Abstract: Sheepgrass (Leymus chinensis) is one of the dominant grass species present on typical steppes of the Inner Mongolia Plateau. However, L. chinensis has developed a dwarfing phenotype in response to the stressful habitat in grasslands that are severely degraded due to heavy grazing. The lack of transcriptomic and genomic information has prohibited the understanding of the transgenerational effect on physiological alterations in clonal L. chinensis at the molecular level in response to livestock grazing. To solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…With rapid progress in the omics’ era, new methods are available for the study of plant–herbivore interaction [ 22 ]. Transcriptomic analysis of cloned L. chinensis showed that grazing had a transgenerational effect on its growth inhibition and led to the development of a dwarf phenotype in response to the severe degradation of the grassland habitat due to heavy grazing [ 23 ]. In addition, transcriptomic analysis of overgrazed L. chinensis showed that most differentially expressed genes (DEGs) were significantly enriched in phenylpropanoid biosynthesis and flavonoid biosynthesis pathways [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…With rapid progress in the omics’ era, new methods are available for the study of plant–herbivore interaction [ 22 ]. Transcriptomic analysis of cloned L. chinensis showed that grazing had a transgenerational effect on its growth inhibition and led to the development of a dwarf phenotype in response to the severe degradation of the grassland habitat due to heavy grazing [ 23 ]. In addition, transcriptomic analysis of overgrazed L. chinensis showed that most differentially expressed genes (DEGs) were significantly enriched in phenylpropanoid biosynthesis and flavonoid biosynthesis pathways [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dwarf forms of long-term grazed L. chinensis may be an adaptation to long-term grazing by large herbivores (Li et al, 2015 ). At the transcriptome and proteome level, the expression of the genes involved in defense and immune responses, pathogenic resistance, and cell development was changed, which collectively inhibited the growth of clonal L. chinensis (Ren et al, 2018a ). Furthermore, the proteins associated with dwarfism induced by OG were also altered, including upregulated ATPB_DIOEL and downregulated DNAK_GRATL, as well as proteins that interact with them, such as RPOB2_LEPTE, A0A023H9M8_9STRA, and RBL_AMOTI, (Ren et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…The size of individual S. grandis plants is minimized to cope with frequent grazing or overgrazing (Wan et al, 2015;Li et al, 2018). The leaf photosynthetic activity, as indicated by net photosynthetic rate, stomatal conductance, intercellular carbon dioxide concentration, and transpiration rate, is markedly decreased following overgrazing (Ren et al, 2017). In recent years, several studies have been conducted to explore the molecular mechanism of plant dwarfism resulting from overgrazing at the transcription and protein levels (Wan et al, 2015;Ren et al, 2018a,b).…”
Section: Introductionmentioning
confidence: 99%